Penggunaan Prosedur Overcorrection Terhadap Perilaku Berlebihan Siswa Autis - Margarice Saroinsong (Jurnal Ilmiah Wahana Pendidikan, 2020)
Autism is seen as (1) a psychological developmental disorder and (2) a neurological development disorder that affects the way a person communicates and relates to others around him. This study aims to analyze the effects of using overcorrection strategies with forced movement exercises on three prominent autistic behaviors, particularly handflowing, handmouthing, handclapping and touching objects in a 7-year-old boy with autism in SLB Berkat Yosua Kamanta. The research method used was an experimental single subject research (SSR) inter-behavior design. The results showed a substantial reduction in the three autistic behaviors with the overcorrecion procedure. The autistic behavior rate decreased by 80%.